Regulatory Private Security in the Former Yugoslavia, With Emphasis on the Recent Changes in Serbia - Nikač, Željko; Korajlić, Nedžad; Ahić, Jasmin; Bećirović, Maida (Kriminalističke teme, 2013)
The subject of this paper is a partial comparative legal analysis of the legislation in the field of private security in the former Yugoslavia, namely the former Yugoslav republics and now independent states, with special emphasis on the recent new regulations in the Republic of Serbia. In terms of methodology, the work is dominated by legal methods - normative and parallel with respect to other methods of scientific research. In terms of systematic work in the introduction to the first gives an overview of the concept of security and subsystem private security and security operators to protect persons and property and their activity. Next follows a review of the major international legal sources of private security, as well as international law, the International Code of Conduct for Private Security Companies, legal rules and regulations of either the EU. In terms of systematic work in the introduction to the first gives an overview of the concept of security and subsystem private security and security operators to protect persons and property and their activity. Next follows a review of the major international legal sources of private security, as well as international law, the International Code of Conduct for Private Security Companies, legal rules and regulations of either the EU. The central part of the paper takes up a presentation on the legal basis of security protection of people and property in the former Yugoslavia, then in the former Yugoslav republics as independent states, and today, finally, the recently adopted regulations in the Republic of Serbia. Serbia was the only country within the former state to adopt regulations governing the private Security - Law on Private Security and the Law on Detective Activity. In a further period of six months is expected to adopt bylaws for the implementation of the regulations, followed by evaluation of initial experiences in the implementation of the rights of private security norms.